2021
DOI: 10.1144/sp513-2020-175
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and Nd–Sr isotopic composition of alkaline lamprophyres from the Early to Late Cretaceous Mundwara Alkaline Complex, NW India: evidence of crystal fractionation, accumulation and corrosion in a complex magma chamber plumbing system

Abstract: The Early to Late Cretaceous Mundwara alkaline complex (comprising the Musala, Mer and Toa plugs) displays a broad spectrum of alkaline rocks closely associated in space and time with the Deccan Large Igneous Province (DLIP) in NW India. Petrology and Nd-Sr isotopic data on two youngest and altogether compositionally different lamprophyre dykes of the Mundwara alkaline complex are presented in this paper to understand their petrogenesis and also to constrain the magmatic processes responsible for generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…700 m in Ramgarh‐1 in the Jaisalmer Basin, NDR database, 2021; maximum 1800 m of Cretaceous recorded in the Jaisalmer Basin, Zadan & Arbab, 2015; <200 m on the Saraswati Terrace, Barmer Basin, Dolson et al, 2015). Strata were then subaerially exposed at the end‐Cretaceous Period when the main Palaeocene rifting in the Barmer Basin took place (Dolson et al, 2015; Millett et al, 2021; Naidu et al, 2017; Sharma et al, 2021; Vijayan et al, 2016). Although it is not possible to be definitive regarding the extent of diagenesis at this unconformity surface, the uplift was of long duration and resulted in the removal of all Upper Cretaceous sediments (Sheth, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…700 m in Ramgarh‐1 in the Jaisalmer Basin, NDR database, 2021; maximum 1800 m of Cretaceous recorded in the Jaisalmer Basin, Zadan & Arbab, 2015; <200 m on the Saraswati Terrace, Barmer Basin, Dolson et al, 2015). Strata were then subaerially exposed at the end‐Cretaceous Period when the main Palaeocene rifting in the Barmer Basin took place (Dolson et al, 2015; Millett et al, 2021; Naidu et al, 2017; Sharma et al, 2021; Vijayan et al, 2016). Although it is not possible to be definitive regarding the extent of diagenesis at this unconformity surface, the uplift was of long duration and resulted in the removal of all Upper Cretaceous sediments (Sheth, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Sheth (2016) and Krishnamurthy (2019) discussed the possibility of the presence of more than one sub‐crustal magma chambers in the evolution of the Deccan lavas. Non‐basaltic rocks (including rhyolites, andesitic tuffs, lamprophyres and andesites) are all common components of the DVP (Agrawal & Upadhyaya, 1991; Cucciniello et al, 2019; Cucciniello et al, 2020; Cucciniello et al, 2022; Krishnamacharlu, 1974; Sharma et al, 2021; Srivastava, 1989). The silicic rocks are considered to have been generated by partial melting of older granitic crust due to the proximity of large volumes of basic magma, but also by fractionation of basic melts (Chatterjee & Bhattacharji, 2008; Cucciniello et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…These primitive diopside cores and their restricted evolution trend (Figure 4) imply the existence of a deeper magmatic chamber that could be connected to the shallow magmatic reservoir represented by the PN massif, in a complex plumbing system [3,30,64]. These relict cores can be classified as antecrysts, crystals that did not crystallize directly from the host magma in which they are contained, although they maintain a genetic relationship with the same system [3,10,29].…”
Section: Antecrysts In the Ponte Nova Massifmentioning
confidence: 99%
“…Although a quantitative determination of P estimates is not possible for the Ti-augite mantling and rim composition, their evolution trend suggests very low-P crystallization conditions (cf., [64,[72][73][74][75]). Ti-augite from all intrusions of PN presents a very positive correlation of Ti and the IV Al (Figure 5) [74] showed that there are compositional differences between high and low pressure clinopyroxenes based on trends of increasing Ti and IV Al at the expense of silica, the increase in the IV Al/ VI Al ratio and the increase in TiO 2 coupled with decreasing Mg# cpx .…”
Section: Estimation Of Intensive Parameters (P-t) For High-mg Diopsid...mentioning
confidence: 99%